C-Reactive Protein Is an Indicator of the Immunosuppressive Microenvironment Fostered by Myeloid Cells in Hepatocellular Carcinoma - Wang, Yongchun; Li, Zhixiong; Huang, Zhijie; Yu, Xingjuan; Zheng, Limin; Xu, Jing (Frontiers in Oncology, 2022)
Background C-reactive protein (CRP) is a widely used marker of systemic inflammation and predicts poor clinical outcomes in patients with hepatocellular carcinoma (HCC); however, its significance in the local immune response at the tumor site is not clear. Methods Serum CRP levels of 329 HCC patients were detected before resection. Paired paraffin-embedded tumor samples were used to quantify immune cell populations, such as CD11b+ myeloid cells, CD68+ macrophages (Mφs), CD15+ neutrophils, CD8+ T cells, and CD206+, CD204+, CD163+ and CD169+ Mφs, by immunohistochemistry. Enrichment scores for 34 types of immune cells based on transcriptome data from 24 HCC samples were calculated by xCell. Overall survival of patients was analyzed using the Kaplan-Meier method. Results Serum CRP levels were correlated with liver functions and tumor stages in patients with HCC. The densities of CD68+ tumor-associated macrophages (TAMs) and CD15+ tumor-associated neutrophils (TANs) were significantly higher in patients with elevated serum CRP levels than in those with low CRP levels (both p < 0.0001). Further analysis of TAM subtypes revealed that serum CRP levels were associated with CD204+ and CD163+ Mφ densities (p < 0.0001 and p = 0.0003, respectively). Moreover, transcriptome data showed that CRP expression was associated with the expression of myeloid cell infiltration-related genes in HCC tumors. The combination of serum CRP with TAMs or TANs in both the nontumor and intratumor regions could represent a powerful criterion for predicting patient prognoses. Conclusion Serum CRP could serve as an indicator of an immunosuppressive TME in HCC, which could be of potential clinical application for treatment strategies targeting the TME.